What are Public Ideas?. (August 2020) - Stapleton, Orla; Sauder, Michael; Hallett, Tim
The authors explore how newspaper articles engaging seven publicly prominent social science ideas develop from ideas in the public to public ideas when mediators and interpretants use them, and oscillate between these uses as part of an unfolding career.